An analysis on the discourse of Powerpoint presentation slides of ESL novice learners / Nurliyana Isa - Isa, Nurliyana (2014)
Creating Powerpoint presentations has now became part of the requirement at tertiary level. As countries are now moving towards achieving knowledge-based workers who are able to compete and perform at the tertiary level and the working world, the requirement in using technology is now a must. However, exposure to all of the linguistic features, structures and conventions of Powerpoint presentations should have begun at a tender age with facilitation from the teachers throughout primary and secondary education. Unfortunately, due to budget cuts and time constraints, many learners did not get the privilege of learning the 'how-to's in using Powerpoint presentations slide. This proved to be an obstacle to these novices at their point of entry into tertiary education as compared to their more experienced comrades. Hence, this discourse study was conducted to shed light onto the linguistic features, structures and conventions displayed by these novices when dealing with Powerpoint presentations. Furthermore, this study serves as a start-up point as it is one of the rare few researches that look into Powerpoint presentation slides through the use of a discourse analysis and a Language Analysis Model by Ellis and Johnson (1994). The study was conducted using two models which are the Ellis and Johnson's (1994) framework and Bhatia's (1993) model. These models were then used to analyze linguistic features, structures and conventions present in the Powerpoint presentation slides. Based on the findings, it was evident that novice learners do show regularity in the features of Powerpoint presentations used pertaining to their rhetorical structure, lexico - grammatical features and conventions. The findings highlighted the errors in signposting and labeling, use of tenses and rhetorical questions, text to visual ratio, selection of lexis as well as organization of Powerpoint presentation slides. The findings congregated could encourage educational institutions to emphasize and incorporate Powerpoint presentation lessons or assessments into classrooms. Furthermore, the findings could aid in understanding the processes, acceptable norms and the workings in regards to Powerpoint presentations. On top of that, it could create awareness on the importance of learning the features that entails a good Powerpoint presentation as this practice will be a life-long skill. It is hoped that, due to the importance of mastery this skill, schools and the Ministry could include this as a compulsory module at school level. This study recommends that future works should be done with gender variation across education level and to include the spoken discourse of the presentation for a more comparative finding.